2023
DOI: 10.3390/jcm12154948
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Diabetes Mellitus Type II (DMII) in the Multiple Sclerosis Population: A Systematic Review and Meta-Analysis

Abstract: Introduction: The interactions between Diabetes Mellitus type II (DMII) and Multiple Sclerosis (MS) lead to higher levels of fatigue, higher risk of physical disability, faster cognitive decline, and in general a lower quality of life and a higher frequency of depression compared to the general population. All of the above accelerate the disability progression of patients with MS, reduce the patients’ functional capacity, and further increase their psychological and economic burden. Methods: This systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…These findings are in accordance with the results of prior population-based cohorts and registries that ascertain an increased risk of MS patients for cerebrovascular and cardiovascular diseases [ 12 , 31 ]. In particular, cardiovascular risk factors were documented with varying prevalence among patients with MS, with crude prevalence estimates for hypertension of 18.2% (95% CI 5.9–35.3%), diabetes: 5.4% (95% CI 2.1–10.2%) and dyslipidaemia: 11.5% (95% CI 2.9–24.7).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in accordance with the results of prior population-based cohorts and registries that ascertain an increased risk of MS patients for cerebrovascular and cardiovascular diseases [ 12 , 31 ]. In particular, cardiovascular risk factors were documented with varying prevalence among patients with MS, with crude prevalence estimates for hypertension of 18.2% (95% CI 5.9–35.3%), diabetes: 5.4% (95% CI 2.1–10.2%) and dyslipidaemia: 11.5% (95% CI 2.9–24.7).…”
Section: Discussionsupporting
confidence: 91%
“…For each dichotomous outcome of interest, the pooled prevalence with 95% confidence intervals (95% CI) was calculated for the aggregate meta-analysis, after the implementation of the Freeman–Tukey variance-stabilizing double arcsine transformation [ 12 – 14 ]. The random-effects model of meta-analysis (DerSimonian and Laird) was utilized for estimation of the pooled estimates [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Notably, research indicates that WC more accurately predicts cardiovascular risk and T2DM in PwMS compared to the BMI, which underestimates adiposity in these patients [ 46 , 47 ]. Moreover, multiple studies have demonstrated a significant association between an increased WC and elevated risks of cerebral small vessel disease, T2DM, and neurological disability [ 48 , 49 ]. Consequently, WC emerges as a more accurate prognostic indicator of the cardiovascular burden in PwMS, which has been linked to an elevated risk of cerebral small vessel disease and neurological disability.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, certain studies have demonstrated that glucose control in patients with MS was not enhanced after 24 weeks of combined endurance and resistance training (Wens et al, 2015). Although the prevalence of type II diabetes mellitus (T2DM) in the MS population is <10%, it rate is still higher than that in the general population (Giannopapas et al, 2023). Moreover, patients with T2DM in the MS population display significantly reduced levels of insulin secretion compared to that of patients without T2DM (Katsuki et al, 1998).…”
Section: Insulin Resistance and Multiple Sclerosis (Ms)mentioning
confidence: 99%